The Relation of Fund Characteristics on Sharia Equity Mutual Funds Performance - Bilhaq Fajrinda; Jubaedah Nawir; Nurmatias Nurmatias (University of Darussalam Gontor, 2022)
This research aims to find out and prove the influence of fund size, fund age, and jakarta islamic index on sharia equity mutual funds performance. The object of the study is sharia equity mutual funds using a sample of 16 mutual fund products during the period 2017-2020 and the use of Data Panel Regression Analysis Techniques through the Eviews 10 program. The results found in the study are fund size, fund age and JII positively affect on sharia equity mutual funds performance.